Balance dilemma: the effect of work-life balance and work stress on turnover intention at ud putra ts, majalengka - Wulandari, Haula; Nurherna, Sri Wina; Nurdiana, Editya (Institute of Computer Science (IOCS), 2025)
In the modern world of work, work-life balance is an important factor in determining employee satisfaction and retention. Imbalances in this aspect often trigger work stress, which can ultimately increase employee turnover intention or intention to leave the organization. This study aims to analyze the influence of work-life balance and work stress on turnover intention at UD Putra TS, an SME in the retail sector in Majalengka. This study uses a quantitative approach with a survey method. Data was collected from 50 employees using a questionnaire with a Likert scale of 5 points. Data analysis was carried out using multiple linear regression with the help of SPSS. Descriptive statistical results show that 64% of employees experience a work-life imbalance, 58% feel high work stress, and 40% have the intention to leave in the next six months. The regression test results showed that work-life balance had a negative and significant influence on turnover intention (? = -0.421, p < 0.05), which means that the better the work-life balance, the lower the employee's intention to leave. On the other hand, work stress had a positive and significant effect on turnover intention (? = 0.507, p < 0.05), which indicated that the higher the level of work stress, the greater the employee's intention to leave the company. These findings are in line with the Job Demands-Resources (JD-R) Theory, which states that the imbalance between job demands and resources can trigger stress and increase turnover intention. These results also support recent research in the past five years, such as studies by Kim & Kao (2021), Wang et al. (2022), and Nugroho & Setiawan (2024), which found similar relationships in the context of SMEs and the retail industry